Pendampingan Manajemen Usaha dan Keuangan Pada UMKM Kue Basah di Kecamatan Kedung waringin - Andi Suhandi; Bayu Umara (JPPI: Jurnal Pengabdian Pelita Insani, 2025)
MSMEs contribute to the National Gross Domestic Product (GDP) and have an important role in Indonesia's economic recovery. Therefore, the form of appropriate business management and financial management is needed to advance an MSME. The purpose of this PKM activity is to provide an understanding of business management so that it has direction, is measurable and well-planned, also regarding financial management, so that planning, management, storage, and control of funds can support the activities and development of MSME partner businesses. The method of implementing this activity is through stages from the start to the implementation stage and the evaluation stage. The results of the implementation of the activity show an increase in progress and development in the business